2019
DOI: 10.7322/jhgd.157746
|View full text |Cite
|
Sign up to set email alerts
|

Relevância diagnóstica dos Gráficos de Recorrência na caracterização de Saúde, Doença ou Morte, em humanos

Abstract: Introduction:Recurrence plots have been increasingly used to evaluate complex dynamic systems of which the human body is an excellent model. The different quantitative and qualitative elements of recurrence plots in health, disease, and death were analysed. A time series of normal heartbeats were collected in healthy newborns, healthy children, healthy young adults, healthy middle-aged adults, elderly individuals living in nursing homes, individuals with advanced chronic kidney disease, and individuals with de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Previously, it was shown that local anesthesia during ophthalmic surgeries increased the HR and LF/HF ratio 17. Another study showed that alphacaine did not significantly influence HRV in subjects undergoing endodontic treatment due to irreversible pulpitis or pulp necrosis of the upper front teeth 38,39,40. Taken together, the aforementioned studies indicate that intraocular anesthesia is unable to increase the vagal influence on heart rhythm.…”
Section: Discussionmentioning
confidence: 88%
“…Previously, it was shown that local anesthesia during ophthalmic surgeries increased the HR and LF/HF ratio 17. Another study showed that alphacaine did not significantly influence HRV in subjects undergoing endodontic treatment due to irreversible pulpitis or pulp necrosis of the upper front teeth 38,39,40. Taken together, the aforementioned studies indicate that intraocular anesthesia is unable to increase the vagal influence on heart rhythm.…”
Section: Discussionmentioning
confidence: 88%
“…The heart rate variability (HRV) is defined as the unpredictability between heart beats and can be separated into various indices of measurement, reflecting ANS influence on cardiac control [7,8]. Furthermore, the indices that reflect the parasympathetic branch of ANS are reduced with the onset of an inflammation process, such as muscle fibrosis in people with DMD, corroborating the position that the sympathetic branch is modulating even during rest periods, and it is related to cardiac events [9] and sudden death [10].…”
Section: Introductionmentioning
confidence: 85%
“…It was observed that dogs younger than one year old (G1) showed sympathetic predominance, with values greater than 0 V and less than 2 V, but this group of animals did not present significantly different values in relation to the dogs in groups 3 and 4; however, the animals that make up G3 (healthy dogs > 8 years) showed values greater than 2 V, showing parasympathetic predominance in these stages of life, but it was noticed that dogs in group 3 and 4, the values of 0 V increased progressively and the of 2 V have decreased. The immaturity of the autonomic nervous system shows a clear physiological decrease in HRV, but aging and the presence of diseases at different stages cause progressive deterioration of autonomic function, gradually reducing HRV (Godoy and Gregório 2019).…”
Section: Discussionmentioning
confidence: 99%